Impact of myocardial revascularization on long-term outcomes in a nationwide cohort of first acute myocardial infarction survivors. (18th May 2022) - De Luca, Leonardo; D'Errigo, Paola; Rosato, Stefano; Mureddu, Gian Francesco; Badoni, Gabriella; Seccareccia, Fulvia; Baglio, Giovanni
Abstract: The long-term clinical benefits of myocardial revascularization in a contemporary, nationwide cohort of acute myocardial infarction (AMI) survivors are unclear. We aimed to compare the mortality rates and clinical outcomes at 8 years of patients admitted in Italy for a first AMI managed with or without myocardial revascularization during the index event. This is a national retrospective cohort study that enrolled patients admitted for a first AMI in 2012 in all Italian hospitals who survived at 30 days. The outcomes of interest were all-cause mortality, major cardio-cerebrovascular events (MACCE), and re-hospitalization for heart failure (HF) at 8 years. Time to events was analysed using a Cox and Fine and Gray multivariate regression model. A total of 127 431 patients with AMI were admitted to Italian hospitals in 2012. The study cohort consisted of 62 336 AMI events, of whom 63.8% underwent percutaneous or surgical revascularization ≤30 days of the index hospital admission. At 8 years, the cumulative incidence of all-cause death was 36.5% (24.6% in revascularized and 57.6% in not revascularized patients). After multiple corrections, the hazard ratio (HR) for all-cause mortality in revascularized vs. not revascularized patients was 0.61 ( P < 0.0001). The rate of MACCE was 45.7% and 65.8% (adjusted HR 0.83; P < 0.0001), while re-hospitalizations for HF occurred in 17.6% and 29.8% (adjusted HR 0.97; P = 0.16) in AMI survivors revascularized and not revascularized, respectively. In our contemporary nationwide cohort of patients at their first AMI episode, those who underwent myocardial revascularization within 1 month from the index event compared to those not revascularized presented an adjusted 39% risk reduction in all-cause mortality and 17% in MACCE at 8-year follow-up.